2017
DOI: 10.14198/jhse.2017.124.12
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of breast motion at different levels of support during physical activity

Abstract: Optical tracking systems have been used in previous studies to capture the motion of the nude breast and breasts in bras, under the assumption that no breast-bra relative movement occurred within the bra. This study compared breast and bra movement through electromagnetic tracking and optical tracking systems to determine the relative breast movement occurring with different breast support and exercise-induced breast discomfort. Total of 30 female participants (mean age: 21.5 ± 2.3 years; cup sizes: A-F) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Numerous biomechanical studies have since confirmed this sinusoidal breast movement pattern, with greater breast displacement found with increased breast mass, vertical torso motion, and lower limb cadence (22,86,97,142,144,164). Conversely, less breast displacement was found when women wore increased external breast support, usually provided by a sports bra (22,51,77,82,84,89,101,116,120,133,143,160,164,166,175,176). Graphs of three-dimensional breast displacement during treadmill running, when women ran with and without breast support, are displayed in Scurr et al (144).…”
Section: How Does the Breast Move?mentioning
confidence: 91%
See 3 more Smart Citations
“…Numerous biomechanical studies have since confirmed this sinusoidal breast movement pattern, with greater breast displacement found with increased breast mass, vertical torso motion, and lower limb cadence (22,86,97,142,144,164). Conversely, less breast displacement was found when women wore increased external breast support, usually provided by a sports bra (22,51,77,82,84,89,101,116,120,133,143,160,164,166,175,176). Graphs of three-dimensional breast displacement during treadmill running, when women ran with and without breast support, are displayed in Scurr et al (144).…”
Section: How Does the Breast Move?mentioning
confidence: 91%
“…Numerous studies have investigated the effects of different breast support conditions on breast motion (22,25,51,58,77,82,84,89,101,105,116,120,132,133,143,160,163,164,166,176,177). These studies have consistently shown that breasts move more when a woman is not wearing any external breast support (bare-breasted) compared with wearing either low external breast support (such as a fashion bra) or high external breast support (such as a sports bra).…”
Section: Figure 3 Perimeter Of the Breast And Its Attachments To The Anterior-lateral Chest Wallmentioning
confidence: 99%
See 2 more Smart Citations
“…Another way of controlling breast displacement is via encapsulation sports bras that separate each breast in designed cups, often with the use of under-wires that lead to a loss of comfort while exercising (Norris et al , 2021). A hybrid-type sports bra design, which combines both compression and encapsulation feature, provides breast elevation and compression at the same time, and has been shown to reduce breast displacement and breast discomfort more efficiently (McGhee et al , 2013; Ching-Sui et al , 2017).…”
Section: Introductionmentioning
confidence: 99%